Single and combined effects of Bacillus spp. and brown seaweed (Sargassum vulgare) extracts as bio-stimulants of eggplant (Solanum melongena L.) growth - Rania AYDI BEN ABDALLAH; Nawaim Ammar; Fakher Ayed; Hayfa Jabnoun-Khiareddine; Mejda Daami-Remadi (Advances in Horticultural Science, 2021)
Bacillus subtilis SV41, B. amyloliquefaciens subsp. plantarum SV65 and Sargassum vulgare extracts were evaluated for their plant growth-promoting potential on eggplant (Solanum melongena L.) plants. Bio-treatments applied singly and/or in combination were further compared to a compost tea and to a commercial bio-fertilizer (Acadian™). Results clearly showed that the combined treatments based on the two Bacillus spp. strains and the aqueous algal extract and the last one mixed with B. amyloliquefaciens subsp. plantarum SV65 induced the highest enhancements in the plant height and the maximum root length which were estimated at 32.4-33.9%, 23.9-25.5% and 23.4-25% and at 36.8-41%, 32.9-37.4% and 36.3-40.5% compared to water, compost tea and Acadian™ based treatments, respectively. Furthermore, the combined treatment based on the aqueous algal extract and B. amyloliquefaciens subsp. plantarum SV65 had significantly improved eggplant growth where the recorded increments in the stem diameter, the aerial part fresh weight, and the root fresh weight varied from 17.5 to 24.6%, 38.4 to 46.1%, and 32.3 to 50% as compared to the three controls, respectively. As for single treatments tested, the aqueous extract had induced a significant improvement in the major growth parameters measured. Developed bio-stimulant was found to be more effective than compost tea and commercial bio-fertilizer based treatments.